Surface electromyography character of upper limb muscle after open reduction combine with ulnar osteotomy in children with neglected Monteggia fracture - Qiu, Hailing; Li, Tingzhi; Li, Fanling; Zhang, Siqi; Wu, Xiangling; Yang, Jing; Li, Xin; Fang, Ke; Wen, Jie; Xiao, Sheng (Frontiers in Pediatrics, 2024)
Objective This study aims to investigate the surface electromyography (sEMG) characteristics of upper limb muscles in children with neglected Monteggia fracture after open reduction of radial head dislocation and ulna osteotomy and bone grafting internal fixation, and to understand the recovery of muscle activity in children after operation, provide reference for clinical rehabilitation. Methods A retrospective analysis was conducted on sixteen children with neglected Monteggia fracture who underwent ulna osteotomy at our hospital from January 2021 to August 2022. The biceps brachii, triceps brachii, flexor carpi radialis, and extensor carpi ulnaris muscle activities were recorded during grip strength tests, flexion and extension of elbow joint while holding a 1 kg dumbbell, as well as gripping tasks. The root mean square (RMS) values of sEMG signals, co-contraction ratio, and elbow joint function scores were compared between pre- and post-operation periods as well as between the affected side and unaffected side. Results The preoperative maximum grip strength, as well as the average RMS values of flexor carpi radialis and average RMS value of extensor carpi ulnaris on the affected side were significantly lower. After surgery, both the maximum RMS value of biceps brachii and maximum and average RMS value of extensor carpi ulnaris on the affected side remained lower. Prior to surgery, when performing elbow flexion and extension tests while holding a 1 kg dumbbell, both mean RMS values of biceps brachii and flexor carpi radialis on the affected side were smaller. However, after surgery, there was an increase in mean RMS values of biceps brachii on the affected side. Furthermore, postoperative elbow function scores were significantly higher than preoperative scores. Conclusion Open reduction of radial head dislocation combined with ulna osteotomy and bone grafting can achieve good functional activities in the treatment of neglected Monteggia fractures in children. The EMG activity of the extensor carnosus ulnalis muscle on the affected side related to grip strength was low, and the desired effect was not achieved within the expected time.